Association of Serum PSP/REG Iα with Renal Function in Type 2 Diabetes Mellitus - Huimin Zhu; Xiangyun Zhu; Hao Lin; Dechen Liu; Yu Dai; Xianghui Su; Ling Li (Journal of Diabetes Research)
Purpose. Pancreatic stone protein/regenerating protein I (PSP/REG Iα) is a secretory protein mainly detected in the pancreas. Recent studies revealed increased serum PSP/REG Iα levels may reflect renal dysfunction. The purpose of this study was to detect the relationship between PSP/REG Iα and renal function in subjects with and without type 2 diabetes mellitus (T2DM). Methods. This cross-sectional study was conducted at Zhongda Hospital, affiliated with Southeast University in China. Serum PSP/REG Iα levels were measured using a method of enzyme-linked immunosorbent assay. Baseline characteristics and biochemical parameters, such as blood urea nitrogen (BUN), serum creatinine (SCr), and uric acid (UA), were collected. The estimated glomerular filtration rate (eGFR) of each individual was calculated using the diagnostic criteria for renal function. Correlations between PSP/REG Iα and renal function parameters were analyzed by Spearman’s rank correlation coefficient using SPSS 20.0 software. Results. Serum PSP/REG Iα levels were significantly higher in T2DM patients than those without T2DM (P<0.05). The level of PSP/REG Iα was positively correlated with age, SCr, and BUN and negatively correlated with eGFR. The ordinal multiple logistic regression analysis further illustrated that PSP/REG Iα levels were negatively related with eGFR in both groups after adjusting for other parameters. Conclusions. Serum PSP/REG Iα level is significantly upregulated in T2DM patients and reflects renal function in both T2DM and nondiabetic control groups. The relationship between PSP/REG Iα and eGFR suggested that PSP/REG Iα might be a potential indicator of renal dysfunction.